Importância da não utilização do coproparasitológico como única ferramenta diagnóstica em cães com diarreia - Gizzi, Aline Baumann Rocha; Biondo, Alexander Welker; Leutenegger, Christian; Marcondes, Mary [UNESP]; Stedile, Rafael; Powolny, David; De Oliveira, Mariana Cordeiro; Braga, Karina Francini; Oliveira, Simone Tostes (My University, 2013)
A total of 147 fecal samples of dogs including 104 diarrheal and 43 normal (control) were analyzed. The samples were submitted to fecal parasitological using the fecal flotation technique for identification of parasite eggs, larvae, cysts and oocysts. Additionally there was a panel of real-time PCR (qPCR) which included the detection of Canine Distemper Virus, Canine Enteric Coronavirus, Canine Parvovirus 2, Clostridium perfringens enterotoxin A, Cryptosporidium spp, Giardia sp. and Salmonella spp. A total of 20/104 (19.2%) and 71/104 (68.3%) of the diarrheal fecal samples and 3/43 (7.0%) and 13/43 (30.2%) of normal samples were positive for the fecal parasitological technique and qPCR, respectively. Dogs positive for helminths were 1.7 times more likely to be positive in the qPCR panel. Considering the qPCR as the gold standard, the fecal parasitological showed only 31.2% sensitivity for the detection of Giardia sp. The study shows the importance of using laboratory techniques such as qPCR panels, able to detect multiple pathogens and fecal parasitological should not be used alone even in cases of positive results.
The importance of not using only the fecal parasitological as a tool diagnostic in dogs with diarrhea
Keywords: Coinfection; Diagnosis; Dog; Feces; Real time PCR; Worms